Evaluation of the Design of Hemodialysis Patient Monitoring System at Lestari Kidney and Hypertension Clinic Semarang - Lutfatila Masitoh; Cahya Tri Purnami; Aris Puji Widodo (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Patients diagnosed with kidney disease are very difficult to accept and are not ready to undergo haemodialysis treatment. Objective: Effectiveness is needed to make patients with chronic kidney disease more obedient to treatment and to ask about kidney treatment and important health information for kidney failure patients. Method: The aim of this research is to evaluate the design of a patient's haemodialysis monitoring system in the Gingival Clinic and the Pressure of Current Lester, by conducting research based on methods and qualitative descriptive types of research. Result: Research has shown that Clinical Kidney and Concurrent Lestari Hypertension require a haemodialysis patient monitoring system to facilitate healthcare in patient monitoring and facilitate physicians in decision making.